Dissociation of tissue uptake of cholesterol ester from that of apoprotein A-I of rat plasma high density lipoprotein: selective delivery of cholesterol ester to liver, adrenal, and gonad. - Glass, C (1983)
The metabolic fate of homologous high density lipoprotein (HDL) was studied in the rat, tracing the apoprotein A-I (apo A-I) and cholesterol ester moieties simultaneously. The apo A-I was labeled with covalently linked 125I-labeled tyramine cellobiose, which accumulates in the cells degrading the apoprotein; [3H]cholesterol ethers, which cannot be hydrolyzed or mobilized after uptake, were incorporated into the lipid core of reconstituted HDL to reflect the fate of the cholesterol esters. Several lines of evidence, including direct comparison with biologically labeled HDL, are presented to support the validity of this approach. The liver was the major organ of cholesterol ether uptake, accounting for 65% of the total; the adrenal gland and ovary were the most active organs per gram (wet) of weight. Uptake of cholesterol ether was 7-fold greater than that of apo A-I in adrenal, 4-fold greater in the ovary, and greater than 2-fold greater in the liver. The remaining tissues took up apo A-I and cholesterol ethers at more nearly equal rates. Transfer of HDL-associated cholesterol ethers and 125I-labeled apo A-I to other lipoprotein fractions was not observed; thus, the results reflect direct uptake from HDL itself. Whereas uptake of low density lipoprotein appears to involve endocytosis of intact particles, uptake of HDL in at least some rat tissues involves additional, more complex, transfer mechanisms.